Risk of SARS-CoV-2 reinfection and COVID-19 hospitalisation in individuals with natural and hybrid immunity: a retrospective, total population cohort study in Sweden. Issue 6 (June 2022) - Nordström, Peter; Ballin, Marcel; Nordström, Anna
Summary: Background: Real-world evidence supporting vaccination against COVID-19 in individuals who have recovered from a previous SARS-CoV-2 infection is sparse. We aimed to investigate the long-term protection from a previous infection (natural immunity) and whether natural immunity plus vaccination (hybrid immunity) was associated with additional protection. Methods: In this retrospective cohort study, we formed three cohorts using Swedish nationwide registers managed by the Public Health Agency of Sweden, the National Board of Health and Welfare, and Statistics Sweden. Cohort 1 included unvaccinated individuals with natural immunity matched pairwise on birth year and sex to unvaccinated individuals without natural immunity at baseline. Cohort 2 and cohort 3 included individuals vaccinated with one dose (one-dose hybrid immunity) or two doses (two-dose hybrid immunity) of a COVID-19 vaccine, respectively, after a previous infection, matched pairwise on birth year and sex to individuals with natural immunity at baseline. Outcomes of this study were documented SARS-CoV-2 infection from March 20, 2020, until Oct 4, 2021, and inpatient hospitalisation with COVID-19 as main diagnosis from March 30, 2020, until Sept 5, 2021. Findings: Cohort 1 was comprised of 2 039 106 individuals, cohort 2 of 962 318 individuals, and cohort 3 of 567 810 individuals. During a mean follow-up of 164 days (SD 100), 34 090 individuals with natural immunity in cohort 1 were registered as having had a SARS-CoV-2 reinfection compared with 99 168 infections in non-immune individuals; the numbers of hospitalisations were 3195 and 1976, respectively. After the first 3 months, natural immunity was associated with a 95% lower risk of SARS-CoV-2 infection (adjusted hazard ratio [aHR] 0·05 [95% CI 0·05–0·05] p<0·001) and an 87% (0·13 [0·11–0·16]; p<0·001) lower risk of COVID-19 hospitalisation for up to 20 months of follow-up. During a mean follow-up of 52 days (SD 38) in cohort 2, 639 individuals with one-dose hybrid immunity were registered with a SARS-CoV-2 reinfection, compared with 1662 individuals with natural immunity (numbers of hospitalisations were eight and 113, respectively). One-dose hybrid immunity was associated with a 58% lower risk of SARS-CoV-2 reinfection (aHR 0·42 [95% CI 0·38–0·47]; p<0·001) than natural immunity up to the first 2 months, with evidence of attenuation thereafter up to 9 months (p<0·001) of follow-up. During a mean follow-up of 66 days (SD 53) in cohort 3, 438 individuals with two-dose hybrid immunity were registered as having had a SARS-CoV-2 reinfection, compared with 808 individuals with natural immunity (numbers of hospitalisations were six and 40, respectively). Two-dose hybrid immunity was associated with a 66% lower risk of SARS-CoV-2 reinfection (aHR 0·34 [95% CI 0·31–0·39]; p<0·001) than natural immunity, with no significant attenuation up to 9 months (p=0·07). To prevent one reinfection in the natural immunity cohort during follow-up, 767 individuals needed to be vaccinated with two doses. Both one-dose (HR adjusted for age and baseline date 0·06 [95% CI 0·03–0·12]; p<0·001) and two-dose (HR adjusted for age and baseline date 0·10 [0·04–0·22]; p<0·001) hybrid immunity were associated with a lower risk of COVID-19 hospitalisation than natural immunity. Interpretation: The risk of SARS-CoV-2 reinfection and COVID-19 hospitalisation in individuals who have survived and recovered from a previous infection remained low for up to 20 months. Vaccination seemed to further decrease the risk of both outcomes for up to 9 months, although the differences in absolute numbers, especially in hospitalisations, were small. These findings suggest that if passports are used for societal restrictions, they should acknowledge either a previous infection or vaccination as proof of immunity, as opposed to vaccination only. Funding: None.